Knowledge and Attitude of Sciatica Pain and Treatment Methods among Adults in Saudi Arabia - Majdi Hashem; Reem Abdulrahman AlMohaini; Norah Ibrahim AlMedemgh; Sara Abdulmajed AlHarbi; Lena Saleh Alsaleem (Advances in Orthopedics)
Background. Sciatica is a relatively common condition, with a lifetime incidence varying from 13% to 40%. The corresponding annual incidence of an episode of sciatica ranges from 1% to 5%. The exact cause of sciatica is unknown to this day; treatment methods and practices differ between individuals based on their cultural background, socioeconomic status, and religious beliefs. This study aimed to assess the knowledge and attitude toward sciatica pain among adults in Saudi Arabia. Methods. A cross-sectional study was conducted among the adult population in Saudi Arabia. A self-administered questionnaire was distributed among the study population using an online survey. Questions were divided into four groups, each containing multiple questions covering the following aspects: demographic data, past medical history, and the assessment of knowledge and attitudes regarding sciatica. Results. A total of 3,764 respondents were involved in this study, with an age range of 18–65 years old (females 59.8%). The mean knowledge score was 3.8 (SD 2.1), with the majority having poor knowledge (60.1%). The most common source of sciatica information was an orthopedic or a neurosurgeon, while the most common self-treatment used was painkiller medications (30.8%). The mean attitude score was 35.8 (SD 5.3), with most respondents having a neutral attitude (80.3%). The factors correlated with an increase in knowledge and attitude were having a bachelor’s or higher degree and living in an urban area. Conclusion. While the attitude of the adult population toward sciatica pain seems adequate, their knowledge was shown to be deficient. Furthermore, when comparing diagnosed individuals living in cities with those in rural areas, both knowledge and attitudes were shown to be better in individuals living in cities. Awareness programs by health institutions and healthcare professionals are needed to enhance patients knowledge. Various media can be utilized to enhance patients knowledge including social media platforms.